Pretreatment protocol of fiber posts before luting procedures - A. S. Bobrovskaia; A. V. Mitronin (LLC "Endo Press", 2020)
Relevance. The use of fiber posts in the post-endodontic restoration is widespread among dental practitioners. However, one of the key disadvantages of this technique is the poor adhesion between the posts and luting cements. The use of various chemical solutions for surface pretreatment, in particular, 37% hydrogen peroxide, makes it possible to achieve acceptable values of adhesion.The goal is to compare the efficiency of fiber post pretreatment with various chemical solutions and to develop an optimal pretreatment protocol.Materials and methods. Evaluation of the adhesive bond strength of the 370 fiberglass pins of 3 different types with 2 types of luting cements, was carried out by torqueout test. Posts were divided into 18 groups depending on the pretreatment method.Results. The highest values of adhesive bond strength were achieved after post treating with concentrated hydrogen peroxide for 10 minutes, followed by silanization.Conclusions. Fiber post pretreatment before luting procedures with chemical solutions that contribute to the dissolution of the polymer matrix increases the adhesive bond strength compared to the control group without pretreatment.